Age-related changes in the metabolization of phosphatidic acid in cerebral cortex synaptosomes - Pasquaré, Susana Juana (2009)
In this study, phosphatidic acid (PA) metabolization is found to generate diacylglycerol (DAG), monoacylglycerol (MAG) and glycerol by the sequential action of lipid phosphate phosphatase (LPP), diacylglycerol lipase (DAGL), and monoacylglycerol lipase (MAGL) in cerebral cortex (CC) synaptosomes. It is also demonstrated that PA is metabolized by phospholipases A (PLA)/lysophosphatidic acid phosphohydrolase (LPAPase) in synaptic endings. Age-related changes in the metabolization of PA have been observed in rat cerebral cortex synaptosomes in the presence of the alternative substrates for LPP, namely LPA, sphingosine 1-phosphate (S1P) and ceramide 1-phosphate (C1P). In addition, LPA and C1P up to concentrations of about 50 μM favor the metabolism in the direction of MAG and glycerol in aged and adult synaptosomes, respectively. At equimolecular concentrations with PA, LPA decreases DAG formation in adult and aged synaptosomes, whereas S1P decreases it and C1P increases it only in aged synaptosomes. Sphingosine (50 μM) or ceramide (100 μM) increase PA metabolism by the pathway that involves LPP/DAGL/MAGL action in aged membranes. Using RHC-80267, a DAGL inhibitor, we could observe that 50% and 33% of MAG are produced as a result of DAGL action in adult and aged synaptosomes, respectively. Taken together, our findings indicate that the ageing modifies the different enzymatic pathways involved in PA metabolization.